The Concept of Justice from the Contractarian Perspective - Załuski, W. (Інститут держави і права ім. В.М. Корецького НАН України, 2005)
Данная статья посвящена анализу научных подходов Канта и Гоббса к идее общественного договора и их влиянию на концепцию справедливости. В статье раскрыто взаимоотношение указанных подходов с двумя разными моделями общественного договора. Показана роль теорий общественного договора в процессе развития понятия справедливости. Автор указал, что относительно теорий общественного договора справедливость может рассматриваться или как взаимная выгода или как беспристрастность. The present article is dedicated to the analysis of the Kantian and the Hobbesian approaches to the idea of the social contract and their influence on the concept of justice. The correlation of these approaches with two different models of the social contract has been shown. The role of the contractarian theories in the process of explication of the notion of justice has been demonstrated. The author points out that according to the contractarian theories justice can be realized either as the mutual advantage or as the impartiality.